Prevalence and predictors of postoperative pneumonia after coronary artery bypass grafting: a single-center registry study - V. S. Kaveshnikov; M. A. Kuzmichkina; A. V. Kaveshnikov; V. Kh. Vaizov; M. O. Ostrovik; V. N. Serebryakova; T. P. Kalashnikova; Yu. A. Arsenyeva; B. N. Kozlov; A. A. Boshchenko (Кардиоваскулярная терапия и профилактика, 2025)
Aim. To assess the prevalence and predictors of postoperative pneumonia (PP) after coronary artery bypass grafting (CABG) based on inhospital registry data.Material and methods. This retrospective study of 925 patients who underwent elective CABG in 2017-2019 based on inhospital registry data. Combined intervention was performed in 11% of cases. PP was diagnosed according to national guidelines. Multivariate logistic regression was used to identify predictors. Preoperative, surgical, and postoperative variables were included in the association analysis.Results. The incidence of PP was 8,7%. PP developed on day 5,5 [3; 8] (Me [Q25; Q75]) after CABG. Sex did not affect the risk. In univariate analysis, significant factors for PP were preoperative white blood cell (WBC) count, aortic cross-clamp time (ACCT), and maximum postoperative creatine phosphokinase (CPK) level. In the multivariate model, the independent nature of predictors was confirmed: preoperative leukocyte count (OR — odds ratio (odds ratio) =1,11; p=0,008), AC duration (OR=1,07; p=0,045), and postoperative CPK level (OR=1,04; p=0,018). Combined surgeries did not increase the risk.Conclusion. PP is a serious complication of cardiac surgery, negatively affecting clinical outcomes and economic aspects of treatment. After CABG, PP was detected in 8,7% of cases in the examined cohort. There were following key predictors: preoperative WBC count, ACCT, and maximum postoperative CPK level. The obtained results indicate the possible benefit of monitoring individual inflammatory markers and minimizing ACCT for predicting and reducing the risk of pneumonia.